Pengaruh Motivasi Belajar terhadap Keterampilan Proses Sains Siswa dalam Pembelajaran Fisika Ditinjau dari Gender - Restu Ramanda; Andika Kusuma Wijaya; Haris Rosdianto (STIKes Ibnu Sina Ajibarang, 2025)
The purpose of this study is to determine the influence between student learning motivation and gender on students' science process skills in physics learning. This study is included in the type of survey with a comparative design and uses a quantitative approach to analyze the relationship between variables. The population in this study is all grade IX students of SMP Negeri 4 Singkawang, data was taken using saturated sampling techniques. The instrument used in this study was a learning motivation questionnaire consisting of 22 statements and science process skills test questions consisting of 10 expanded multiple-choice questions. The data analysis technique used in this study is the two-way ANOVA Test. The results of the hypothesis test show that. (1) There is no difference in students' science process skills based on learning motivation in physics learning. (2) There is no difference in students' science process skills based on gender in physics learning. (3) There is an influence of student learning motivation and gender on students' science process skills in physics learning. With a sig value > 0.05 for hypotheses (1) and (2), while a sig value < 0.05 for hypothesis (3). From the explanation above, it can be concluded that individually, learning motivation and gender do not affect students' science process skills. But the combination of these two variables affects students' science process skills in physics learning.